Palimpsests with Hélène Cixous: Experiments with Oneself - Bejarano, Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Our reflection is interested in the language(s) inhabited by the writer and philosopher Hélène Cixous through our experience in her classes and the continuous reading of her characteristically hibrid and open works. This dialogue with her work includes our own experience with writing in the form of a palimpsest, interwoven with senses and sensations of the word and its resonance.